Surreptitious practices in the management of persons with serious mental illnesses – Perspectives from the schizophrenia research foundation - Ramachandran, Padmavati (Medknow Publications & Media Pvt Ltd, 2012)
The aim of this communication is to briefly describe the surreptitious practices and management of non-adherence, observed at the services offered by the Schizophrenia Research Foundation. Screening of records at our services for documentations of this practice and the efforts made to deal with non-adherence and concealed treatment was done. Surreptitious practices in SCARF's out-patient services and in community outreach programs have been documented. Efforts to manage non-adherence include educating families on pharmacotherapy and strategies of dealing with non-adherence. At the level the patient, individualised and group strategies deal with the issues addressing lack of insight, acceptance of the disorder, or dealing with perceived side effects are held. Ethical principles of autonomy, justice, beneficence, and respect are adopted in implementing these strategies. There are potential advantages and disadvantages of adopting surreptitious treatment strategies in persons with serious mental illnesses. There is a need to formulate rigorous guidelines for the management of non-adherence.